If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + -67 = 164 Reorder the terms: -67 + r = 164 Solving -67 + r = 164 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '67' to each side of the equation. -67 + 67 + r = 164 + 67 Combine like terms: -67 + 67 = 0 0 + r = 164 + 67 r = 164 + 67 Combine like terms: 164 + 67 = 231 r = 231 Simplifying r = 231
| 2-z/2.05=-15 | | 1.5f-5=1 | | m-157=597 | | -3.75y=8 | | 11y=550 | | 2/7(4m-18=12 | | 60+c+90=180 | | 17v=102 | | 8y-7-4y=74-5y | | 7(2x-11)=3(2x-4)+7 | | 13v=559 | | 2(4+3r)-3(r+1)=11 | | (x^2)/(x^2-9) | | 10x^4/5x^3 | | 3x^4=243equation | | 24-30=a | | (W+2)(w+5)=40 | | 2u+2v=10 | | 27=6x^2+1.5x | | -9-3x=14+2x | | 754x=26390 | | 3(a+9)=3(a-5) | | x/1/2=-3/4 | | 265-9= | | 7.52x+4.83(25-x)=158.41 | | 126-26n=238 | | 6=6x-1.2 | | 2/3y^2=54 | | 3(12-g)=g+8 | | -10x+2y=-3 | | 3x+1=8.5 | | 15e+2=y |